allograft inflammatory factor 1 functions as a pro-inflammatory cytokine in the oyster, Crassostrea ariakensis. - Ting Xu; Jiasong Xie; Baojian Zhu; Xiao Liu; Xinzhong Wu (PLoS ONE)
The oyster Crassostrea ariakensis is an economically important bivalve species in China, unfortunately it has suffered severe mortalities in recent years caused by rickettsia-like organism (RLO) infection. Prevention and control of this disease is a priority for the development of oyster aquaculture. Allograft inflammatory factor-1 (AIF-1) was identified as a modulator of the immune response during macrophage activation and a key gene in host immune defense reaction and inflammatory response. Therefore we investigated the functions of C. ariakensis AIF-1 (Ca-AIF1) and its antibody (anti-CaAIF1) in oyster RLO/LPS-induced disease and inflammation. Ca-AIF1 encodes a 149 amino acid protein containing two typical Ca2+ binding EF-hand motifs and shares a 48-95% amino acid sequence identity with other animal AIF-1s. Tissue-specific expression analysis indicates that Ca-AIF1 is highly expressed in hemocytes. Significant and continuous up-regulation of Ca-AIF1 is detected when hemocytes are stimulated with RLO/LPS (RLO or LPS). Treatment with recombinant Ca-AIF1 protein significantly up-regulates the expression levels of LITAF, MyD88 and TGFβ. When anti-CaAIF1 antibody is added to RLO/LPS-challenged hemocyte monolayers, a significant reduction of RLO/LPS-induced LITAF is observed at 1.5-12 h after treatment, suggesting that interference with Ca-AIF1 can suppress the inflammatory response. Furthermore, flow cytometric analysis indicated that anti-CaAIF1 administration reduces RLO/LPS-induced apoptosis and necrosis rates of hemocytes. Collectively these findings suggest that Ca-AIF1 functions as a pro-inflammatory cytokine in the oyster immune response and is a potential target for controlling RLO infection and LPS-induced inflammation.